Determination of geometrical parameters of the diamond gear hones for the finishing of gears - Michael Storchak; Yuriy Danylchenko (Mechanics and Advanced Technologies, 2019)
The formation of the service properties of the gears occurs at the stages of their finishing using processes such as gear grinding, shaving, gear honing, lapping, etc. The main task of the synthesis of technological systems for the gears finishing processing is to determine the optimal parameters and structure of the technological system that provide the specified properties of gears. One of the first stages of the synthesis of technological systems for the gears finishing processing is the determination of the tool geometric parameters. To determine these parameters, a complex of software-implemented algorithms for their calculation has been developed. Using the example of rolling gear tools such as diamond gear hones, an analysis of the influence the independent characteristics of machine engagement on the area of the tool geometric parameters existence is carry out. Based on this analysis, a model of the tool geometry machine engagement with the machining gear was developed. This model is an integral part of the synthesis of technological systems for the gears finishing processing. As a result of this model functioning, the geometric parameters and optimal shapes of the diamond gear hones working layer have been synthesized